Acknowledgment of Reviewers - Smith, Ken G. (Academy of Management Review, 1999)
The author acknowledges the support of scholars who have contributed their time to the reviewing of manuscripts for the scholarly periodical “Academy of Management Review.” The editors and staff of the Academy of Management Review thank the many scholars who have contributed their time and expertise to review manuscripts for AMR. The following 408 individuals served as external “ad hoc” reviewers during the period July 1998 to June 1999, including all special issues during this time. Thank you for your service!